2011
DOI: 10.1186/1687-2770-2011-37
|View full text |Cite
|
Sign up to set email alerts
|

Multiple positive solutions for a class of quasi-linear elliptic equations involving concave-convex nonlinearities and Hardy terms

Abstract: In this paper, we are concerned with the following quasilinear elliptic equationwhere Ω ⊂ ℝ N is a smooth domain with smooth boundary ∂Ω such that 0 Ω,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The property of the Nehari manifold was used to prove the existence of multiple positive solutions for ( 1.4 ). Furthermore, Hsu [ 11 , 12 ] improved and complemented the main results obtained in [ 10 ]. Recently, Goyal and Sreenadh [ 13 ] investigated a class of singular N -Laplacian problems with exponential nonlinearities in .…”
Section: Introductionmentioning
confidence: 63%
“…The property of the Nehari manifold was used to prove the existence of multiple positive solutions for ( 1.4 ). Furthermore, Hsu [ 11 , 12 ] improved and complemented the main results obtained in [ 10 ]. Recently, Goyal and Sreenadh [ 13 ] investigated a class of singular N -Laplacian problems with exponential nonlinearities in .…”
Section: Introductionmentioning
confidence: 63%
“…They showed that there exists falsemml-overlineλ¯ MathClass-rel> 0 such that ( E λ ) admits at least two positive solutions for λ MathClass-rel∈()0MathClass-punc,falsemml-overlineλ¯, a positive solution for λ MathClass-rel= falsemml-overlineλ¯, and no positive solution for λ MathClass-rel> falsemml-overlineλ¯. For a more detailed reference on this subject, we refer the interested reader to .…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the findings mentioned earlier, we are interested in the existence of multiple positive solutions of without condition . Moreover, we will suppose f ( x , u ) a nonhomogenous case in , and thus, the method of the decomposition of Nehari manifold, which is used in , is not applicable for . Our problem is not only nonlocal and degenerate but also is studied in an unbounded domain.…”
Section: Introductionmentioning
confidence: 99%